A cross-sectional survey and follow up study on major dairy health problems in large and small scale urban farms in Mekelle, Tigray, Ethiopia - Tedla, Mebrahtu (BMC Res Notes, 2018)
OBJECTIVE: This study was conducted with the objective of estimating the incidence of major dairy health problems in the area. RESULT: From a cross-sectional survey (n = 475) and follow up study (n = 68), an overall incidence of 43.00 and 29.02% was reported respectively. This study showed biting fly (9.51%), respiratory problems (7.80%), mastitis (5.13%), actinomycosis (5.12%), dystocia (4.42%), endoparasites (3.81%), retention fetal membrane (3.63%), tick infestation (2.91%), lameness (2.94%), vaginal and uterine prolepses (2.51%), skin related problem (1.70%) and abortion (1.70%) were the main dairy health problems identified. In addition, the follow up study revealed; retention fetal membrane (5.91%), tick infestation (5.91%), respiratory problem (2.91%), mastitis (2.94%), endoparasites (2.94%), lameness (2.94%), dystocia (2.94%), actinomycosis (1.53%) and skin related problems (1.53%). The incidence of dairy reproductive problems showed statistically significant variation among local and cross breeds (P < 0.05). Incidence of infectious diseases among dairy cows managed under intensive and semi-intensive management systems showed a significant difference (P < 0.05). Moreover, incidence of physical injury was also showed a significant difference among animal breeds and management system (P < 0.05). However, reproductive problems among management system and infectious diseases among breeds showed a significant difference (P > 0.05). Overall, this study showed dairy animals are exposed to various type of diseases.